Tolerability of subcutaneous immunoglobulin 20%, Ig20Gly, in pediatric patients with primary immunodeficiencies. (10th January 2019) - Paris, Kenneth; Haddad, Elie; Borte, Michael; Brodszki, Nicholas; Dérfalvi, Beáta; Maródi, Laszlo; Hussain, Iftikhar; Darter, Amy; Engl, Werner; Leibl, Heinz; McCoy, Barbara; Yel, Leman
Aim: To assess Ig20Gly tolerability in pediatric patients with primary immunodeficiencies.Patients & methods: Infusion parameters and tolerability were analyzed in pediatric patients (aged 2–5 years [n = 6], 6–11 years [n = 22] and 12–17 years [n = 22]) receiving Ig20Gly in two Phase II/III trials.Results: Of 2624 Ig20Gly infusions, >99% did not require any rate reduction, interruption or discontinuation due to adverse events (AEs). Median maximum infusion rates and volumes/site were higher in patients 12–17 years of age (30 ml/h/site; 30 ml/site) versus 6–11 years (20 ml/h/site; 15 ml/site) and 2–5 years (18 ml/h/site; 14 ml/site). Rates of causally related systemic and local AEs (0.009 and 0.063 AEs/infusion) were low.Conclusion: Ig20Gly infused at relatively high rates and volumes was well tolerated in children.